Splatoon. Vol. 15 - Hinodeya, Sankichi; Miyaki, Tetsuichiro; Turnage, Bryant; Hinodeya, Sankichi (San Francisco, CA : VIZ Media, LLC, 2022)
Team Blue engages in their most complicated Turf War yet as they combat the Shadows, whose personalities are mirror reflections of Team Blue's own! The result of the challenge will determine the fate of Inkopolis Square!
Translated from the Japanese.
Book reads from right to left in the traditional Japanese format.
Rated A: All Ages; Parental Advisory: Splatoon is rated A and is suitable for all ages--Colophon.
Based on the hit Nintendo video games--Back cover.
5-8
Keywords: Contests -- Comic books, strips, etc; Contests -- Juvenile fiction; Squids -- Comic books, strips, etc; Squids -- Juvenile fiction; Humorous stories; Contests -- Fiction; Squids -- Fiction; Humorous comics; Graphic novels; Paintball (Game) -- Fiction; Paintball (Game) -- Comic books, strips, etc; Teamwork (Sports) -- Fiction; Teamwork (Sports) -- Comic books, strips, etc -- Juvenile fiction; Manga; Comics (Graphic works)